AN ANALYSIS OF EFL STUDENTS’ WRITING ABILITY TO ENHANCE THEIR MICRO AND MACRO WRITING SKILL - Mantra, Ida Bagus Nyoman; Widiastuti, Ida Ayu Made Sri (International Journal of Linguistics and Discourse Analytics, 2019)
Assessing is a process of giving score and evaluation of students’ learning achievement to provide the opportunity to plan further learning improvement to attain the learning standard determined by the curriculum. This study dealt with analyzing students’ writing ability to enhance their micro and macro writing. An ex-post facto research design was employed to establish reliable findings. The research instrument that was used to collect the data was in the form of a productive test. Students were assigned to construct a descriptive paragraph consisting of at least seven sentences. The result of this study showed that: there were 5% of students who achieved an excellent score in writing a descriptive paragraph, 37.5% of students attained good achievement, 30% of students attained sufficient achievement, 17.5% students obtained insufficient achievement, 10% students were in poor achievement. This finding suggests that there still many students found difficulty in writing unified and coherent paragraphs.